World Englishes - Melchers, Gunnel; Shaw, Philip (Great Britain Hodder Education, 2011)
World Englishes Second Edition provides an overview of the global variation in vocabulary, grammar, phonology and pragmatics of English and includes coverage of spoken varieties that have only recently been researched, as well as changes occurring due to the increasing use of English by non-natives internationally.
The roots of English -- The spread of English -- Variation in English -- The inner circle -- The outer circle -- The expanding circle -- Beyond the circles.
Includes bibliographical references (pages 230-248) and index.
Keywords: English language -- Variation; English language -- Variation -- English-speaking countries; English language -- Variation -- Commonwealth countries; English language -- Variation -- Foreign countries; English language -- English-speaking countries; English language -- Commonwealth countries; English language -- Foreign countries